Adherence towards medication among hypertensive patients / Norazli Syarifah Aziz - Aziz, Norazli Syarifah (2008)
Hypertension is a chronic disease which generally requires long term pharmacological therapy and is the third most common cause of death in Malaysia. It is one of the most prevalent chronic diseases and is a major risk for cardiovascular diseases. Non adherence towards medication is the main cause contributing towards poorly controlled hypertension. Adherence towards antihypertensive medications therefore, is paramount in order to achieve the goal of therapy (blood pressure is controlled) and avoid any possible complications of cardiovascular diseases. This study was set out to investigate adherence towards medication among hypertensive patients in the Klang Valley, Malaysia. A cross sectional and descriptive study design was employed by using convenience sampling. About 250 questionnaires were distributed throughout the retail pharmacies by using drop off method as well as approaching the participants. A total of 163 ( 65 .2%) respondents completed the questionnaires of which 52.1 % female and 47.9% male. Adherence towards medication were assessed by using general questions with a modification of the MUAH questionnaires with factors-related adherence. The statistical analysis was carried out using Statistical Package for Social Sciences (SPSS) (version 12.0). It was found that most of the respondents adhered to their medication therapy. Among the 163 hypertensive patients, 65.7% (n=107) of them took medication daily and 92% (n=l 50) of them did not take medication excessively. Based on factors related adherence, most of them had positive attitude, better discipline and less aversion towards medication. This study also demonstrated the association between gender and factors-related adherence; attitude towards medication, discipline towards medication and aversion towards medication. Generally, both genders exhibited similar attitude towards antihypertensive medication and aversion towards medication. However, males had better discipline towards medication than their opposite gender. Although sample size was small, this study found that adherence towards the antihypertensive drugs is high in Malaysia.